Lietuvos aukšto meistriškumo sportininku IL-6 ir VEGFA genetiniu variantu reikšme raumenu darbingumui - Gineviciene, V.; Anikeviciute, G.; Žažeckyte, G.; Sivaciova, M. O. (Sporto Mokslas-Sport Science, 2023)
Different genetic elements and environmental factors influence the muscular performance and physical capacity of athletes. Significant variants in the human genome that are associated with various components of physical performance have already been identified. However, it is not completely clear what molecular mechanisms determine the regulation of the muscle contraction process. Research shows that during physical work, myokines such as interleukin 6 (IL-6, coded by the IL6 gene) and vascular endothelial growth factor A isoform (VEGF-A, coded by the VEGFA gene) are released into the bloodstream during muscle contraction, and concentration of which increases in the blood serum depending on the duration and intensity of physical exercise. The positive effect of these myokines is manifested in vascular endothelium, muscle capillarization, hypertrophy, and metabolism. IL6 and VEGFA gene expression is significantly increased during physical activity, especially endurance performance. It is believed that IL6 rs1800795 and VEGFA rs2010963 polymorphisms may be related to the physical performance characteristics of professional athletes. Therefore, the aim of this case control association study was to investigate and evaluate the impact of IL6 G/C (rs1800795) and VEGFA C/G (rs2010963) genetic variants on the physical capacity of Lithuanian elite athletes. The sample of subjects consisted of 205 Lithuanian athletes of various sports and 205 non-athletes from the general Lithuanian population (control group). The athletes were divided into three groups according to the duration, and specifics of the sport. Genotyping was performed using allelic discrimination real-time polymerase chain reaction method by TaqMan® technology. Based on Hardy and Weinberg equilibrium, the genotypes frequency distribution in the study groups was evaluated. Comparison of allele and genotype frequencies between groups was performed using Fisher`s or Pearson`s x^2 test. Binary logistic regression was used to determine the odds ratio. Statistical data analysis was performed using R Studio 4.1.1 and SPSS (IBM SPSS v.21) programs. The results of the study showed that the frequency of VEGF rs2010963 polymorphism genotypes and alleles in the study groups did not differ significantly (p > 0.05), but IL6 rs1800795 genotypes significantly differed in the team sports group compared to the control (GG/GC/CC: 16.7%, 66.7%, 16.7% vs. 35.1%, 43.4%, 21.5%, p < 0.01). Binary logistic regression analysis showed that the IL6 heterozygous GC genotype more than doubled the odds of becoming a professional team sport athlete (OR = 2.6; 95% CI: 1.46-4.67; p < 0.005). This case-control association study showed the relationship between IL6 rs1800795 polymorphism and the physical performance of Lithuanian team sports athletes. The probability of becoming a professional athlete depends on IL6 rs1800795 (GC genotype). Although the VEGFA rs2010963 polymorphism analysis did not show significant differences between the study groups, we believe that this genetic variant has an additive effect and is important in the training of endurance athletes. The IL6 rs1800795 and VEGFA rs2010963 variants should be further investigated in a larger cohort of athletes and controls, and the association needs to be confirmed or refuted in other world populations.